2019
DOI: 10.1177/1538574418823379
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Carotid Endarterectomy and Carotid Artery Stenting When Performed by a Single Vascular Surgeon

Abstract: Objectives: Carotid artery endarterectomy (CEA) and carotid artery stenting (CAS) are 2 effective treatment options for carotid revascularization and stroke prevention. The long-term outcomes of Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) reported similar stroke and death rate between the 2 procedures. This study presents the short-and longterm outcomes of CEA and CAS of all risk patients performed by a single vascular surgeon in a real-world setting. Methods: We retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The study cohorts ranged from 65 to 6940 patients. All articles presented the results of observational, retrospective, comparative studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The studies' characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study cohorts ranged from 65 to 6940 patients. All articles presented the results of observational, retrospective, comparative studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The studies' characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of asymptomatic carotid disease was higher in both groups (79.8% in CAS and 64.8% in CEA). In CAS, embolic protection was used in 3911 patients (90.1%), while in four studies the use of a filter or other protection device was not recorded [11,19,22,25].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of large RCTs, it can be clearly stated that, among the long-term outcomes, there is no significant difference between CEA and CAS in the incidence of ipsilateral stroke [2,6,7,12,13]. However, concerning restenosis, the literature data are rather contradictory; while RCTs have shown that CAS has a higher rate of restenosis [2,14,15], observational studies have noted that CEA has a higher rate of restenosis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, conventional CAS does not remove plaque but seeks to stabilize the potentially embolic lesion by covering it with a layer of the metallic stent and subsequent stable fibrous tissue layer (healing). 7 One of the major causes of ischemic complications after stent deployment in patients with unstable plaques is PP through stent struts. Open-cell stent devices have a higher risk of periprocedural stroke compared with closed-cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, conventional CAS does not remove plaque but seeks to stabilize the potentially embolic lesion by covering it with a layer of the metallic stent and subsequent stable fibrous tissue layer (healing). 7…”
Section: Introductionmentioning
confidence: 99%